Cameroon : Review of the Staff-Monitored Program and Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility, and for Additional Interim Assistance under the Enhanced Heavily Indebted Poor Countries Initiative. (IMF Staff Country Reports; Country Report, 2005)
The staff report for the Review of the Staff-Monitored Program and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility highlights economic developments and performance. Fiscal consolidation efforts were sustained, and public finances improved markedly in the first half of 2005, exceeding the Staff-Monitored Program (SMP) targets. IMF staff welcomes the improvements made in public financial management and urges the government to persist in its efforts. The government encountered some technical difficulties, but also was not able to fully implement other SMP commitments.